Long-term effects of health shocks and insurance on rural households’ consumption and wealth in Vietnam: evidence from panel data - Völker, Marc; Kanchanachitra, Manasigan (Journal of Public Health and Development, 2021)
Evidence of the impact of health coverage on households’ financial security in the event of health shocks in Vietnam has been limited by a focus on public insurance and short-term shock experience. Therefore, we examined the impact of public and private insurance coverage, interacted with health shock experience over multiple years, on the consumption and wealth of rural households. Drawing on a representative sample of 1,876 rural households from three provinces in Vietnam, we show that, in the absence of health coverage, health shocks have a positive effect on health expenditures while reducing non-health expenditures and wealth. Public health coverage decreases the probability to incur health expenditures in the event of longer-term health shocks. Among households incurring health expenditures, public health coverage reduces the amount of health expenditures incurred within three years after the onset of an illness. Private health insurance mitigates reductions in non-health expenditures and wealth which can occur more than one year after a health shock. Our findings suggested that Vietnam’s public health coverage program needs improvement in terms of expanding the benefit package and/or reducing the proportion of cost sharing to effectively protect rural households from both short-term and longer-term financial risks including a decrease in non-health consumption and wealth associated with health shocks. Private health insurance can be a safeguard from the longer-term financial risks of illness, for those with access to it.